Diagnóstico del clima laboral en la Cooperativa de Ahorro y Crédito Calceta limitada. - Cedeño Rendón, Gabriela Maricela (2018)
The present investigation was developed in the Credit Union Limited Sock and had as objective to diagnose the labor climate in order to contribute to the improvement of competitive activities, focusing on the needs of the employees of the entity. For this applied techniques such as the interview and survey where they made a number of questions to 31 employees that unveiled the labor situation in the company. Ran through the application of three main phases where developed in stages and activities. To be considered in the first instance the characterization of the entity then formed a group of experts by implementing the Delphi method to determine the coefficient of competence to then select and identify the most relevant variables for the measurement of workplace climate, and propose actions for improvement. The diagnosis was executed by performing a synthesis of the data obtained, showing clearly and precisely the interpretation of the results, in which they met the variables that are in deficiency and in this way determine the causes and effects reflecting them in the tool 5W+1h the results conclude that the applied study evidence a work climate in a level of compliance on a regular basis. To give a solution to the deficiencies found developed a plan for improvement to combat potential problems and find positive responses in the determination of the variables of the labor climate.